USULAN PENENTUAN LOKASI GUDANG EKSTERNAL PRODUK FARMASI MENGGUNAKAN METODE CENTER OF GRAVITY DI JAWA BARAT : STUDI KASUS DI PT. GPO SUMEDANG - Krismono Fauzi Agianto; Mira Yanto; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
Distribution creates a smooth flow of marketing and is a link between production and consumption activities. Pharmaceutical companies that can distribute products to their customers quickly according to the time, number and conditions that have been agreed will get more attention from their customers compared to companies that cannot meet it. To achieve the best distribution, it is necessary to place a good distribution center. The Center of Graivty method is used to determine the location of a new external warehouse based on the coordinate point of the distributor or customer of PT. GPO. The results of the research location of distribution centers are -6.653153379 and 107.5731519 located in Karangpedas Village, Kiarapedes District, Purwakarta Regency. The total distance reduction obtained from this study was as far as 145.43 km. The total cost of transportation is assumed to be directly proportional to the distance traveled, so that with the reduction of total mileage, transportation costs will also be smaller